Review of CGIAR's Open Access/Open Data Policy and implementation support - Keizer, Johannes; Madalli, Devika (CGIAR Independent Evaluation Arrangement, 2018)
The purpose of the review was to assess to what extent the OA/DM Policy has been adopted and implemented during the transition period and its likelihood to be effective in terms of achieving its intended purpose of maximizing global accessibility of CGIAR research. The focus was on assessing the intent, appropriateness, clarity, and coverage of the Policy and the effectiveness of support provided. The review provided lessons from the first years of supporting the implementation of the Policy and recommendations for enhancing full compliance and the efficiency and the effectiveness of the Policy.